Savings, Investment, and Growth in Eastern Europe - Montiel, Peter (IMF Working Papers; Working Paper ;, 1991)
Even modest investment rates may achieve satisfactory rates of growth in the reforming economies of Eastern Europe because their relative capital scarcity implies high rates of productivity for capital. The most serious obstacle to private investment is uncertainty about the reform process, which can potentially rule out all but the most profitable projects. This problem sharply increases the payoff from accelerating the structural reform process. Regarding savings, critical aspects are the changes in methods of financing resulting from economic reform, and the availability of foreign savings, both in the form of loans and foreign direct investment.